Strengthening a Sustainable Quality Culture in Education through School Self-Evaluation - Yulia Suprehatin; Siti Julaiha (Al-Qalam Institue, 2025)
This article examines the strategic role of School Self-Evaluation (SSE) in strengthening a sustainable quality culture in educational institutions. The main objective of this study is to analyze how SSE functions as an internal quality assurance mechanism capable of identifying institutional strengths and weaknesses while guiding continuous improvement efforts. Using a literature review method, this article synthesizes research findings, policy documents, and theoretical perspectives related to educational quality, quality assurance systems, and school-based evaluation practices. The results indicate that SSE provides schools with valid and comprehensive data for decision-making, supports evidence-based planning, and promotes collaborative reflection among school stakeholders. Furthermore, SSE contributes to the development of a sustainable quality culture by embedding consistent monitoring, evaluation, and follow-up actions within school management processes. However, challenges such as limited evaluator competence, insufficient understanding of instruments, and resistance to change may hinder its optimal implementation. The findings imply that capacity building, stakeholder involvement, and policy support are essential to maximize the impact of SSE on school quality improvement.